Shifting and Variational Properties for Fourier-Feynman Transform and Convolution - Byoung Soo Kim (Journal of Function Spaces)
Shifting, scaling, modulation, and variational properties for Fourier-Feynman transform of functionals in a Banach algebra S are given. Cameron and Storvick's translation theorem can be obtained as a corollary of our result. We also study shifting, scaling, and modulation properties for the convolution product of functionals in S.